2017
DOI: 10.1186/s12883-017-0902-6
|View full text |Cite
|
Sign up to set email alerts
|

A case of neuropsychiatric lupus Erythematosus characterized by the Owl’s eye sign: a case report

Abstract: BackgroundSystemic lupus erythematosus (SLE) is an autoimmune inflammatory disorder characterized by multiple affected systems. More than half of SLE patients will suffer from neuropsychiatric lupus erythematosus (NPSLE) during the course of their disease. Although nearly half of the NPSLE patients have normal MRI manifestations, the abnormalities found in the remainder can be located anywhere in the brain, and especially in the subcortical white matter of the frontal and temporal lobe. However, NPSLE involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is that 28%-40% of adult SLE patients' experince NPSLE before diagnosis and/or during SLE diagnosis. After 1 year of being SLE diagnosis, it was reported that 63% develop NPSLE [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is that 28%-40% of adult SLE patients' experince NPSLE before diagnosis and/or during SLE diagnosis. After 1 year of being SLE diagnosis, it was reported that 63% develop NPSLE [3].…”
Section: Introductionmentioning
confidence: 99%